Zoflox, an Antibacterial Drug, in Treatment of Infectious Pathologic Processes in the Lower Respiratory Tract Complicating Acute Respiratory Viral Infection in Elderly Patients - L. V. Zueva (Антибиотики и Химиотерапия)
Clinical trial of Zoflox, an antimicrobial drug, was performed in complex therapy of elderly outpatients with acute pneumonia complicating acute respiratory viral infection. Among the outpatients there were elderly subjects with hepatic insufficiency. The drug showed to be efficient and safety when used in a middle therapeutic dose of 400 mg twice a day daily for 10-14 days.